Evaluation of inverter reconnection for large solar parks - Chernet, Selam (My University, 2010)
The growing demand in energy consumption as a result of both accelerated growth in human population and advancement in technology is exerting tremendous stress on our environment. Majority of electrical production are typically provided from fossil fuels like coal, natural gases and oil which contribute highly to the increasing CO2 production. To reduce the negative impact of these resources and reduce the societies dependency on them, sustainable, renewable energy resources like biomass, geothermal, solar, wind, ocean thermal, wave action and tidal action have come into focus. This master thesis looks into the improvement of efficiency of large solar parks. The work investigates the application of inverter reconnection mechanisms of solar inverters applied to large solar park. This is performed by modeling the possible switching mechanisms in Mat lab and analyzing the loss reduction potential of each inverter reconnection. The loss profile of solar inverter is derived from datasheet values available for a 100KW and 500KW Gamesa Inverter. To generate the output from the solar park, two types of commercial available photovoltaic simulation softwares were used namely PVSyst 5.12 and INSEL 8. To incorporate the effect of shading on the performance of solar park, the work also investigates modeling of large solar parks. Three mathematical models were investigated and the results are presented. The implementation of the model was done in Mat Lab. The modeling for large solar parks is performed in order to investigate the performance of the inverter reconnection with respect to partial shading. Since measurement setups weren’t available, none of the models can be verified with measured data. The model results confirm theoretical analysis.
Keywords: Elkraftteknik; Electric power engineering